Introduction of participatory budget - Писаренко, В. П. (Scientific Progress & Innovations, 2016)
The article is devoted to the introduction of participatory budget developed and approved with the participation of the public, the financial plan, the overall control realized by citizens and local authorities. We formed definition, determined participants and target groups. Foreign experience in implementing participatory budgeting is given. We formed conclusions concerning the formation of high-level intellectual reasonableness of solutions through broad participation of the masses in the process of their adoption.